(untitled) (Al-Academy, 2023)
The study of cultural identity and its data in the designer’s work is considered a cultural nature to highlight the cultural identity and link it to the national culture of their country and society. It provides a reflection and translation of the society’s culture, traditions, social and economic dimensions, the natural environment, and scientific phenomena. Within meanings translated into a variety of methods, including expressive and realistic, which defines the designer’s relationship with his society and the national culture of his country and his connection with the civilization of the country.The research problem came with the following question: What are the data of cultural identity in the work of designer David Gentleman? while the researcher identified four chapters for this study as follows:The first chapter to clarify the methodological framework of the research, while the second chapter represented the theoretical framework and by two chapters: the first included the concept of cultural identity in graphic design, while the second topic included the diversity of identity in the designer’s work, while the third chapter represented the research procedures, and the fourth chapter included the results and conclusions, including: 1. The designer’s thought is formed from the cultural identity of his country and society, and therefore the designer has an important role in the image of his design product of the character.2. The religious identity had a clear impact on the designer’s style, which affected the process of artistic production of stamps.3. The nature of the designer’s interaction with his environment, with all its factors, reflects the achievement of an environmental identity (natural) in the character designs.